UNDERSTANDING SENSEX DYNAMICS IN THE INDIAN STOCK MARKET - Singh, Naib; Ahuja, Shagun (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The stock market or exchange is a vital platform where buyers and sellers come together to trade securities. Transactions in the stock market are guided by an index which reflects the price movements of selected securities and serves as a key market indicator. In India, the stock market has become a significant focus of the government’s economic strategy. Only listed securities are traded on stock exchanges and companies must meet specific regulatory requirements to list their securities. At the Bombay Stock Exchange (BSE), the primary index used to measure fluctuations in security prices is the Sensex. The Sensex serves as the benchmark for trading and reflects the overall performance of the market. It is composed of companies selected based on criteria such as liquidity, trading volume and industry representation. As such, the Sensex provides investors with a reliable guide for making informed investment decisions.